2021
DOI: 10.1002/cne.25098
|View full text |Cite
|
Sign up to set email alerts
|

Acute Δ9‐tetrahydrocannabinol prompts rapid changes in cannabinoid CB1 receptor immunolabeling and subcellular structure in CA1 hippocampus of young adult male mice

Abstract: The use and abuse of cannabis can be associated with significant pathophysiology, however, it remains unclear whether (1) acute administration of Δ‐9‐tetrahydrocannabinol (THC) during early adulthood alters the cannabinoid type 1 (CB1) receptor localization and expression in cells of the brain, and (2) THC produces structural brain changes. Here we use electron microscopy and a highly sensitive pre‐embedding immunogold method to examine CB1 receptors in the hippocampus cornu ammonis subfield 1 (CA1) 30 min aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 86 publications
(120 reference statements)
0
14
0
Order By: Relevance
“…4A, B). In addition, there was significant CB1 background staining, presumably reflecting CB1 receptors in pyramidal cells and glia cells (Bonilla-Del Río et al, 2021). CB1R-axons had a higher bouton density and higher bouton turnover compared to CB1R+ axons (Fig.…”
Section: Cb1 Receptors Regulate Inhibitory Bouton Dynamics Specifically In Cb1r+ Axonsmentioning
confidence: 91%
See 2 more Smart Citations
“…4A, B). In addition, there was significant CB1 background staining, presumably reflecting CB1 receptors in pyramidal cells and glia cells (Bonilla-Del Río et al, 2021). CB1R-axons had a higher bouton density and higher bouton turnover compared to CB1R+ axons (Fig.…”
Section: Cb1 Receptors Regulate Inhibitory Bouton Dynamics Specifically In Cb1r+ Axonsmentioning
confidence: 91%
“…CB1 receptors are G-protein coupled receptors and are widely abundant in the brain. They are expressed in both excitatory and inhibitory neurons, as well as in glia cells (Bonilla-Del Río et al, 2021;Hebert-Chatelain et al, 2016;Maroso et al, 2016;Navarrete et al, 2014). Perhaps the most prominent CB1 expression is in a subset of inhibitory axons in the dendritic layer of the hippocampal CA1 area (Bonilla-Del Río et al, 2021;Dudok et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in the CA1 region of male mice have demonstrated that acute THC can increase the percentage of CB1 terminals forming symmetric synapses and increase the area of pyramidal cell dendrites but decrease the size of dendritic spines (Bonilla‐Del Río et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in the CA1 region of male mice have demonstrated that acute THC can increase the percentage of CB1 terminals forming symmetric synapses and increase the area of pyramidal cell dendrites but decrease the size of dendritic spines (Bonilla-Del Río et al, 2020). However, it is unknown whether acute THC induces changes in the hippocampal opioid system and whether these changes are sex-specific.…”
Section: Introductionmentioning
confidence: 99%